2013
DOI: 10.1097/scs.0b013e3182a12f95
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Laryngitis Accompanied by Ramsay Hunt Syndrome

Abstract: The most common presentation of herpes zoster in the head and neck region is called Ramsay Hunt syndrome (RHS), which rarely accompanies multiple cranial neuropathy. Herpes zoster also involves the mucous membrane of the tongue, palate, pharynx, and larynx. Herpes zoster infection of the larynx accompanied by Ramsay Hunt syndrome with cranial polyneuropathy is extremely rare, with only few reported cases in the literature. At the time of this report, a review of the medical literature disclosed 4 reported case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…RHS with multiple CN palsy has rarely been reported. [13][14][15] Kim, et al 3) reported 11 patients with 10 years of RHS with polyneuritis, and the frequency of CN involvement was VII, VIII, IX, X, and V in that order. Shim, et al 13) reported 11 cases for 15 years, and the following CN VII, VIII nerves, the frequency of other CN was CN X, IX, and V in that order.…”
Section: Discussionmentioning
confidence: 96%
“…RHS with multiple CN palsy has rarely been reported. [13][14][15] Kim, et al 3) reported 11 patients with 10 years of RHS with polyneuritis, and the frequency of CN involvement was VII, VIII, IX, X, and V in that order. Shim, et al 13) reported 11 cases for 15 years, and the following CN VII, VIII nerves, the frequency of other CN was CN X, IX, and V in that order.…”
Section: Discussionmentioning
confidence: 96%
“…Previously the literature described cases of RHS concurrent with VZV encephalitis [12] , syndrome of inappropriate secretion of antidiuretic hormone [13] , and laryngitis [14] , but to our knowledge no previous cases of concurrent RHS and disseminated herpes zoster have been reported. Here, we describe a patient with relapsed chronic lymphocytic leukemia (CLL) being treated with ibrutinib (a selective inhibitor of Bruton's tyrosine kinase) who presented with concurrent RHS and disseminated herpes zoster.…”
Section: Introductionmentioning
confidence: 83%
“…The etiology of the laryngitis was unclear, and it could have been caused by patient’s underlying CLL, a drug reaction, or herpes zoster. In a previous case or herpes zoster laryngitis and RHS, combination therapy with steroids and antiviral agents was recommended [14] . Given the severity and the lack of clarity of the etiology of laryngitis, our patient was treated with high dose corticosteroids in addition to acyclovir therapy.…”
Section: Discussionmentioning
confidence: 99%
“…RHS is characterized by the involvement of the geniculate ganglion of the VII nerve and typically presents with a facial nerve palsy and vesicles in the ipsilateral external auditory canal. Although the VIII nerve is frequently co-involved, resulting in the development of dizziness and hearing loss, multiple lower cranial nerve involvement due to RHS has rarely been described [3] ; available reports in the literature include zoster laryngitis related to RHS with cranial polyneuropathy [4] , [5] , [6] , RHS involving the facial and superior laryngeal nerves in a patient with chronic renal disease [7] , RHS involving the VII, VIII and X cranial nerves in an immunocompetent individual [8] , severe dysphagia due to RHS involving the cranial nerves V, VII, VIII, X, and XII [9] , and RHS complicated by seven cranial nerve involvement (V, VII, VIII, IX, X, XI, and XII) [10] .…”
Section: Discussionmentioning
confidence: 99%